If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11+3x-7=6x+5=3x
We move all terms to the left:
11+3x-7-(6x+5)=0
We add all the numbers together, and all the variables
3x-(6x+5)+4=0
We get rid of parentheses
3x-6x-5+4=0
We add all the numbers together, and all the variables
-3x-1=0
We move all terms containing x to the left, all other terms to the right
-3x=1
x=1/-3
x=-1/3
| -6+9p=8p | | 12−6(8u−5)=−54 | | 2-5(x+10)=6+3x | | 4(x+3.29)=11.16 | | -9p=9-8p | | 2(x+2)=110 | | -7i(-8i)=0 | | 10(-2x-3)=6(-2x-9) | | 7(4w+2)/3=-8 | | 4x-24=3x=21 | | 50+3.7=50-1.9x | | 84-12y=180 | | –6+9p=8p | | -3(7.5x)=5(1.5x) | | 3x+5+5x=25 | | -10r-20=−10r−20 | | 1x+9=5x(x+3) | | n/9=-74 | | 19x-14=x+886 | | 2x+15=7/8 | | (2x+-11)(3x+7)=0 | | 24=-s+46 | | 13x+4=-19x+20 | | –12y+–8=16 | | -4|7-6k|=-14 | | (2(x-4)+3)=8 | | -8+x=38 | | 1+6x=-7+7x | | 5x+3=9(x+1) | | 56=-2g+70 | | 37=20x=117 | | 57+3x=60+9=14 |